1991
DOI: 10.1159/000226972
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Estrogen Receptors in Paraffin Sections of Human Thyroid Tissues

Abstract: The optiomal demonstration of estrogen receptor binding in thyroid tissues was made under conditions of 10% protease in 50 mM Tris-HCl buffer (pH 7.6) for 10 min as the pretreatment digestion step, incubation of primary antibody (ER-ICA monoclonal kit; Abbott Laboratories) at 37 °C for 2 h and incubation of secondary antibody (ABC kit; Vector) at 37 °C for 40 min. Thyroid tissues used for assessing the reaction were 17 cases of goiter, 25 adenoma cases, 27 cases of papillary carcinoma, 14 cases of follicular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Further more, ER antibody binding was demonstrated by 30.4% of follicular carcinomas but only 16.5% of papillary le sions and by none of the anaplastic carcinomas studied. The results are generally in line with earlier reports of ER in thyroid tissue studied biochemically [12][13][14][15] or immunohistochemically [15][16][17][18], For example, Takeichi et al [18] described ER immunoreactivity, located in the nuclei, in all of 6 welldifferentiated papillary cancers, 5 of them (83.3%) having 20 or more ER-immunoreactive (ER-IR) cells per lightmicroscope visual field ( x 100). Of the poorly differen tiated papillary cancer cases, 5 (83.3%) had 1-19 ER-IR cells per visual field.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Further more, ER antibody binding was demonstrated by 30.4% of follicular carcinomas but only 16.5% of papillary le sions and by none of the anaplastic carcinomas studied. The results are generally in line with earlier reports of ER in thyroid tissue studied biochemically [12][13][14][15] or immunohistochemically [15][16][17][18], For example, Takeichi et al [18] described ER immunoreactivity, located in the nuclei, in all of 6 welldifferentiated papillary cancers, 5 of them (83.3%) having 20 or more ER-immunoreactive (ER-IR) cells per lightmicroscope visual field ( x 100). Of the poorly differen tiated papillary cancer cases, 5 (83.3%) had 1-19 ER-IR cells per visual field.…”
Section: Discussionsupporting
confidence: 89%
“…This was followed by rinsing in Tris-buffer, incubation in diaminobenzidine for 2 min, washing in tap water and light counterstaining with hematoxylin. ER staining was seen in the nuclei as described in our previous report [16].…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…4], Conventional bio chemical methods have been able to infer the presence or absence of both androgen or estrogen receptors in prostat ic disease, but the exact localization and level of receptor positive cells within differing tissues has been impossible to determine [5][6][7], With the recent development of commer cially available monoclonal antibodies against estrogen receptors (ER), it has been shown that a considerable number of ER-positive cells are to be found among the periglandular fibrocytes, in smooth muscle, and in hyper plastic basal epithelium but not in secretory epithelial [8][9][10]. This may be a phenomenon related to tissue and cellular specificity of binding and technical methods; we have been able to demonstrate optimal binding of anti body to F.R in paraffin-embedded sections of human thy roid [ 11 ]. In the present study, we have evaluated and com pared the ER receptor levels in human tissues from cases of benign prostatic hypertrophy (BPH) and prostate car cinomas, including 15 samples ofcarcinoma from patients undergoing endocrine therapy.…”
Section: Introductionmentioning
confidence: 80%